Definition of Autism and Autism Spectrum Disorder - Eren, R.B.; Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
This chapter addresses the definition of autism spectrum disorder (ASD). A distinction is made between a clinical (medical) definition of ASD as defined in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and an educational eligibility classification of autism found in the Individuals with Disabilities Education Improvement Act (IDEA). The increase of prevalence of ASD is discussed with an opportunity to ponder the reason for this phenomenon. Several theories of causation of ASD are presented, offering an opportunity for thoughtful consideration of these theories found in current literature. General characteristics of ASD are described in the three domains of social interaction, communication, and behavior and are further illustrated by specific behaviors commonly seen in today’s classrooms. Characteristics focus not only on the variety of challenges individuals on the spectrum face but also the strengths many individuals with ASD bring to the classroom and community at large. Finally, a discussion of the future for individuals on the spectrum is emphasized through the wide range of possible outcomes for these individuals. Future opportunities seem to be improving for this population, although there remains a dearth of research on outcomes for adults with ASD. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed